The longitudinal impact of diet, physical activity, sleep, and screen time on Canadian adolescents' academic achievement: An analysis from the COMPASS study - Faught, E.L.; Qian, W.; Carson, Valerie; Storey, K.E.; Faulkner, Guy; Veugelers, P.J.; Leatherdale, S.T. (Elsevier, 2019)
Adequate amounts of physical activity, sleep, and screen time along with a healthy diet have been demonstrated to have positive associations with academic achievement. No longitudinal study has investigated the simultaneous relationship between all of these behaviours and academic achievement. Data from 11,016 adolescent participants of the COMPASS study in Alberta and Ontario were analysed. Students self-reported their adherence to Canadian recommendations for health behaviours and academic achievement in Math and English on school-based surveys administered in the 2015/16 and 2016/17 waves of COMPASS. Multinomial generalized estimating equations were used to evaluate the association between longitudinal changes in adherence to recommendations and academic achievement at follow-up. Models were adjusted for self-reported sociodemographic information, body weight status, and baseline academic achievement. Students who adhered to a greater number of recommendations performed better than students who adhered to fewer recommendations. Meeting recommendations for Meat and Alternatives (protein-rich foods) and screen time were consistently associated with higher academic achievement compared to students who did not meet these recommendations. A change from not meeting recommendations for Vegetables and Fruit to meeting the recommendation in the following year was associated with higher achievement in both subjects. There was no association between sleep behaviours or physical activity and academic achievement. Results indicate that adherence to recommendations for protein-rich foods, screen time, and vegetables and fruit show promise as behavioural targets for higher academic achievement among youth. Further study using objectives measurements of behaviours and further consideration of socioeconomic variables is merited.
The final publication is available at Elsevier via https://doi.org/10.1016/j.ypmed.2019.05.007. © 2019. This manuscript version is made available under the CC-BY-NC-ND 4.0 license http://creativecommons.org/licenses/by-nc-nd/4.0/
Keywords: adolescent health; diet; physical activity; screen time; sleep; academic achievement; childhood obesity; school health